2021
DOI: 10.1051/mfreview/2021014
|View full text |Cite
|
Sign up to set email alerts
|

Multi-response optimization in wire electrical discharge machining (WEDM) of D2steel using utility approach

Abstract: Wire electrical discharge machining (WEDM) is a popular non-conventional machining process used particularly for making extrusion dies, blanking punches, and tools especially requiring tight dimensional tolerances. Because of the process limitation, the rate of cutting and maintenance of close dimensional tolerance is a challenging task. Given the above facts, the present work has been focused on achieving the maximum possible cutting rate (VC) maintaining good dimensional accuracy and corner radius (RC). In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…As a result, research on WEDM over nickel-based alloys and stainless steel offers potential [58,59]. The investigations on nontraditional machining, Taguchi method, and grey relational analysis can be carried out to find the best optimum solutions [60][61][62][63].…”
Section: Surface Roughnessmentioning
confidence: 99%
“…As a result, research on WEDM over nickel-based alloys and stainless steel offers potential [58,59]. The investigations on nontraditional machining, Taguchi method, and grey relational analysis can be carried out to find the best optimum solutions [60][61][62][63].…”
Section: Surface Roughnessmentioning
confidence: 99%
“…Some research results have shown the effectiveness of the combination of the Taguchi method with some multi-objective decision techniques. And the simplicity of the combination of Taguchi À Utility in the multi-objective decision in EDM has contributed to overcome the above limitations [26]. The single-objective and multi-objective optimization problems in EDM are solved by Taguchi method and Taguchi À Grey relational analysis (GRA) [27].…”
Section: Introductionmentioning
confidence: 99%